FACTORS ASSOCIATED WITH THE EFFECTIVENESS OF THE Y-V TECHNIQUE IN EYELID RECONSTRUCTIVE SUGERY (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze factors associated with the effectiveness of the Y-V advancement technique in medial canthoplasty for the correction of epicanthal folds combined with other eyelid abnormalities.Subjects and methods: A prospective interventional study without a control group was conducted on 31 patients (62 eyes). All patients underwent medial canthoplasty using the Y-V advancement technique to correct epicanthal folds, in combination with surgical management of associated eyelid abnormalities, including ptosis, entropion, asymmetric eyelid crease, or absent eyelid crease. Patients were followed up and evaluated 3 months postoperatively.Results: After 3 months of follow-up, 83.9% of eyes achieved good outcomes and 16.1% achieved fair outcomes. Surgical outcomes were significantly associated with age group, severity of the epicanthal fold, and intercanthal distance. The presence of concomitant ptosis did not significantly affect surgical results.Conclusions: Medial canthoplasty using the Y-V advancement technique is a safe and effective procedure, providing significant functional and aesthetic improvement in the management of epicanthal folds, with or without associated eyelid abnormalities.
Keywords: Epicanthal fold, eyelid abnormalities, Y-V advancement technique, blepharoplasty.